VDC_100102370166.0X000001. Issue 2 (February 2018) - Morano, William F.; Gleeson, Elizabeth M.; Sullivan, Sean H.; Padmanaban, Vennila; Mapow, Beth L.; Shewokis, Patricia A.; Esquivel, Jesus; Bowne, Wilbur B.
Appendiceal mucoceles (AMs) are rare mucin-containing neoplasms with malignant potential. Lack of evidence-based data exists defining clinicopathological features for management. MEDLINE search between 1995 and 2015 was performed using search criteria "Appendix mucocele." Systematic review of patient-, pathologic-, and treatment-related characteristics was performed and data analyzed. Among 276 cases of non-perforated AMs, 163 (59%) patients were female, with variable and nonspecific presentation. Patients were treated with appendectomy (52.1%), right hemicolectomy (17.6%), partial cecectomy (17.2%), and ileocecetomy (13.1%). Pathologic evaluation revealed the following: cystadenoma/low-grade appendiceal mucinous neoplasm (54%), unspecified/benign (25%), retention cyst (14.1%), cystadenocarcinoma (4.2%), and mucosal hyperplasia (2.9%). All 11 (4.2%) patients with cystadenocarcinoma were female ( P = 0.004), odds ratio for malignancy 1.07 times higher for women. Synchronous colonic malignancy was reported in three patients (27%) with cystadenocarcinoma ( P = 0.007), odds ratio of 12.1. AMs have low risk for malignancy. Treatment should begin with appendectomy-only and subsequently guided by pathologic diagnosis.